Serial Stimulated Jitter Analysis In Juvenile Myasthenia Gravis. Issue 5 (2nd October 2018) - Bhatia, Shivani; Quinlan, Haley; McCracken, Courtney; Price, Eric W.; Guglani, Lokesh; Verma, Sumit
ABSTRACT: Introduction : Clinical and electrophysiological studies to measures disease activity in juvenile myasthenia gravis (JMG) are limited. Methods : Retrospective review of the clinical profile, Myasthenia Gravis Foundation of America (MGFA) scores, serial stimulated jitter analysis (Stim‐JA) of the orbicularis oculi muscle, grip strength, and spirometry of patients with JMG who were followed in a multidisciplinary clinic was performed. Results : Thirteen patients with JMG (9 females) with mean age of 13.2 ± 4.8 years and follow‐up duration of 25.3 ± 8.3 months (range, 6–39) with ≥ 2 Stim‐JA recordings were included. The mean jitter, mean percentage of apparent single‐fiber action potentials (%ASFAP) with increased jitter, and mean %ASFAP with blocking at baseline values (77.3 ± 54.7 µs, 64.3% ± 35.8%, 39% ± 38.6%, respectively) and at follow‐up (53 ± 45.4 µs, 51.2% ± 34.5%, 17% ± 29.4%, respectively) were abnormal; however, no statistically significant interval difference was noted. The electrophysiological data correlated significantly with Myasthenia Gravis Foundation of America (MGFA) class. Grip strength and spirometry did not correlate with MGFA class. Discussion : Stimulated jitter values are sensitive biomarkers in JMG. Muscle Nerve 58 : 729–732, 2018